“GALICIAN CALIFORNIA” IN THE PROSE OF IVAN FRANKO - Szymonik, Danuta (Porównania, 2013)
The famous Ukrainian writer Ivan Franko (1856–1916) paid much attention to the presentation of the oil industry in Boryslav in his rich and varied creative works. He presented his vision of “Galician California” in short stories (cycle Boryslav, 1877), as well as thematically connected novels Boa constrictor (1879) and Boryslav laughs (1882). These literary works are an artistic unity of theme, characters, form of creation and symbolism of space. As Florian Nieuważny had rightly noticed, Franko as the first had brought the theme of working people to Ukrainian and even east-Slavonic literature which he depicted in a realistic convention taking into consideration forms of artistic conditionality. His experience of Boryslav’s continuum with its social stratification is connected with the experience of a “crossroad” of different national and cultural discourses in above mentioned literary works.